Aeroporto de Fortaleza : usos e significados contemporâneos - Maciel, Wellington Ricardo Nogueira (2006)
The aim of this research is to analyze the contemporary processes of urban changes in the city of Fortaleza. We have as an empirical reference the Airport of Fortaleza which was built within the period of 1996 – 1998. We try to understand the various material and symbolic investments accomplished all around the Airport by the social actors (governmental representatives, tourist trade, architects, inhabitants of the surroundings and “topiqueiros”), who have the Airport as a reference for their social activities. The hypothesis defended in this research is that the successive amplifications/constructions of the Airport throughout the years have been acting in movements accomplished by people who live in the “surrounded areas” which demonstrate, partly, how the subjects have distinct power over the contemporary means of transportation. We even interpret the present-day airport as a partial aspect of the image of the tourist city which is granted to the city of Fortaleza, also as a landscape of power which seems to condense, very well, the present-day conflicts between market and place. We also intend to demonstrate that what the construction of equipments, which are considered as of international quality, such as the present-day airport, seems to illustrate, is one of the exigencies defended by the proponents of the so called urban strategic planning which have predominated among professionals and managers of the cities through decades. In the state of Ceará such strategy was begun more intensively in 1995, with the PRODETUR (An action Program which at the development of Tourism in the Northeast of Brazil).